If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(8x + 1) = 12(1 + 2x) + -9 Reorder the terms: 3(1 + 8x) = 12(1 + 2x) + -9 (1 * 3 + 8x * 3) = 12(1 + 2x) + -9 (3 + 24x) = 12(1 + 2x) + -9 3 + 24x = (1 * 12 + 2x * 12) + -9 3 + 24x = (12 + 24x) + -9 Reorder the terms: 3 + 24x = 12 + -9 + 24x Combine like terms: 12 + -9 = 3 3 + 24x = 3 + 24x Add '-3' to each side of the equation. 3 + -3 + 24x = 3 + -3 + 24x Combine like terms: 3 + -3 = 0 0 + 24x = 3 + -3 + 24x 24x = 3 + -3 + 24x Combine like terms: 3 + -3 = 0 24x = 0 + 24x 24x = 24x Add '-24x' to each side of the equation. 24x + -24x = 24x + -24x Combine like terms: 24x + -24x = 0 0 = 24x + -24x Combine like terms: 24x + -24x = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| -4(8k+4)-5(3k-8)=71 | | N-33=66 | | x^2+8x+q=0 | | 93+x+5=180 | | 8(8p-8)=192 | | 4x-30+60-2x=180 | | 15x+5=2(x+7)+13x | | -168=2(8p-7)+6p | | 5x+3y=650 | | -24=4n-8 | | F(3)=-7x+14 | | 16=4(b-3)+7(4+4b) | | -12x=5x+3 | | 180=3x-6+3x-6+2x | | 0.4x+0.1=4.5 | | 5y-7=63 | | 7(4n+4)=-140 | | 6b-1=50 | | log(4)(6-2x)=1 | | 15x+9=-15x+20 | | 130+134+x=180 | | 3n-9=30 | | 8=7+15x+3x+9x | | 2x+4-7y=0 | | 85=7-3(-2+3n) | | 6h+9t=59 | | 3(2x-4)+12=-6 | | 4(6x-7)(4x+7)=0 | | 2x+18=-6x+14 | | 8=15x+7+3x+9x | | -(x^2)+x-1=0 | | 3bc-6bd= |